(untitled) (Journal of actual problems of jurisprudence, 2019)
Person, provided the legal system of constitutional guarantees , which include guarantees of the right to a dignified and secure life , can fully develop , operate and function in the system of social relations . In Kazakhstan, the interests of individuals are regulated by sectoral system of domestic law and a certain level of integrity. Rights and freedoms of man and citizen occupy one of the first sections of the Basic Law and establishes priorities of the entire state system of the country . However , the inviolability of dignity as we are not talking about self-sufficient category , its truly democratic nature requires constant scientific, practical and dialectical development , taking into account all developing social relations , the role and status of the individual values . Key words: dignity, inviolability of dignity, identity, torture.